2009
DOI: 10.4244/eijv5i5a94
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of patient characteristics and 30-day mortality outcomes after transcatheter aortic valve implantation and surgical aortic valve replacement for the treatment of aortic stenosis: a two-centre study

Abstract: Aims: It is unclear whether transcatheter aortic valve implantation (TAVI) addresses an unmet clinical need for those currently rejected for surgical aortic valve replacement (SAVR) and whether there is a subgroup of high-risk patients benefiting more from TAVI compared to SAVR. In this two-centre, prospective cohort study, we compared baseline characteristics and 30-day mortality between TAVI and SAVR in consecutive patients undergoing invasive treatment for aortic stenosis. Methods and results: We pre-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…In our group, we consider this issue when the Kernel probability density estimate permanently drops below 0.5, but we are not aware of a generally agreed cut-off. In any case, long thin tails of PS that spread near the null point indicate a high probability of residual confounding (here biological rather than chronological age, frailty, severity of comorbid conditions), which may severely distort results, as indeed was the case here 6 : conventional analyses with multivariable adjustment indicated a threefold increase in the odds of death with TAVI as compared with SAVR (OR 3.05, 95% CI: 1.09 to 8.51) at 30 days 6 , when the only randomised trial available at the time indicated a trend towards a lower overall mortality at 30 days with TAVI as compared with SAVR (OR 0.53, 95% CI: 0.24 to 1.14) 14 . Figure 1B shows the distribution of PS in an observational comparison of two cardioplegic solutions used in patients undergoing SAVR at our centre (unpublished).…”
Section: Visual Inspectionmentioning
confidence: 90%
See 4 more Smart Citations
“…In our group, we consider this issue when the Kernel probability density estimate permanently drops below 0.5, but we are not aware of a generally agreed cut-off. In any case, long thin tails of PS that spread near the null point indicate a high probability of residual confounding (here biological rather than chronological age, frailty, severity of comorbid conditions), which may severely distort results, as indeed was the case here 6 : conventional analyses with multivariable adjustment indicated a threefold increase in the odds of death with TAVI as compared with SAVR (OR 3.05, 95% CI: 1.09 to 8.51) at 30 days 6 , when the only randomised trial available at the time indicated a trend towards a lower overall mortality at 30 days with TAVI as compared with SAVR (OR 0.53, 95% CI: 0.24 to 1.14) 14 . Figure 1B shows the distribution of PS in an observational comparison of two cardioplegic solutions used in patients undergoing SAVR at our centre (unpublished).…”
Section: Visual Inspectionmentioning
confidence: 90%
“…Two simple approaches are also specified in Table 2. Our group has only little experience with these approaches 6 , and we are unaware of clear evidence to suggest that these methods are superior to PS matching and IPTW.…”
Section: Use Of Propensity Scores For Adjustmentmentioning
confidence: 99%
See 3 more Smart Citations